2010
DOI: 10.1038/jhh.2010.46
|View full text |Cite
|
Sign up to set email alerts
|

How to simplify the diagnostic criteria of hypertension in adolescents

Abstract: Diagnosis of hypertension in adolescents is complicated because blood pressure values vary with age, gender and height. How can we simplify the diagnostic criteria for hypertension in adolescents? In 2006, anthropometric measurements were assessed in a cross-sectional population-based study of 3136 Han adolescents aged 13-17 years. Hypertension was defined according to the 2004 National High Blood Pressure Education Program Working Group definition. The following equations for blood pressure-to-height ratio (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
96
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(107 citation statements)
references
References 18 publications
9
96
2
Order By: Relevance
“…16 The BPHR index, standardized for height, is strongly and positively associated with SBP and DBP but is not related to age, so it is not dependent on height or age. 9 Our results confirmed the previous findings and established nationwide cutoffs for the BPHR index for detecting hypertension in Chinese children.…”
Section: Discussionsupporting
confidence: 81%
“…16 The BPHR index, standardized for height, is strongly and positively associated with SBP and DBP but is not related to age, so it is not dependent on height or age. 9 Our results confirmed the previous findings and established nationwide cutoffs for the BPHR index for detecting hypertension in Chinese children.…”
Section: Discussionsupporting
confidence: 81%
“…The population we studied was comparable for age and anthropometric parameters with the Chinese sample by Lu and co-workers 1 . As in Chinese population, we found stage 1 hypertension to be more common, whereas, the prevalence of hypertension was higher in our population (15 vs 6%).…”
mentioning
confidence: 98%
“…In a recent issue of this journal, Lu and co-workers 1 found that blood pressure/height ratio (BPHR) was a simple and accurate index for screening hypertension in Han adolescents. However, they suggested that this index had to be validated in other ethnic groups.…”
mentioning
confidence: 99%
“…[14] Different cutoff for SBPHR as 0.73 in males and 0.71 in females, for DBPHR as 0.47, 0.48 in males and 0.45, 0.46 in females were taken. [14] Some other cutoff as per one Chinese study [15] for SBPHR as 0.75, 0.81 in males and 0.78, 0.84 in females, for DBPHR as 0.48, 0.57 in males and 0.51, 0.63 in females were also taken. For all these cutoffs, sensitivity and specificity were calculated.…”
Section: Exclusion Criteriamentioning
confidence: 99%
“…[14] The optimal thresholds of SBPHR/DBPHR for defining HTN (stage I) were 0.75/0.48 for boys and 0.78/0.51 for girls, and for defining HTN (stage II) were 0.81/0.57 for boys and 0.84/0.63 for girls. [15] Aims and Objectives of Study 1. To study BMI in pre-hypertensive and normotensive medical students 2.…”
Section: Introductionmentioning
confidence: 99%